Dissolution time test of effervescent denture cleaner tablets containing 6.5% cocoa fruit peel (Theobroma cacao L.): Uji waktu larut pembersih gigi tiruan tablet effervescent kulit buah kakao (Theobroma cacao L.) 6,5% - Mohammad Dharma Utama; Maqhfirah Amiruddin; Chusnul Chotimah; Andi Tenri Biba; Rina Angraini Utami (Makassar Dental Journal PDGI Makassar, 2026)
The dissolution time test aims to determine the length of time it takes for effervescent tablets to dissolve in a solvent medium. Effervescent tablets made from cocoa bean shells (Theobroma cacao L.) contain flavonoids, saponins, and catechins, which prevent pellicle adhesion and glucan formation by Strepto-coccus mutans, thereby inhibiting the growth of Candida albicans on acrylic resin dentures. This study discusses the dissolution time of KBK effervescent tablets with a concentration of 6.5%. This study is a true experimental study using 16 samples of effervescent tablets tested with a disintegration tester after immersion in distilled water. The results showed that the average dissolution time of KBK tablets was 133 seconds with a standard deviation of 8.07, while that of alkaline peroxide effervescent tablets was 191.38 seconds with a standard deviation of 6.80, indicating a significant difference (p-value 0.000; <0.05). It was concluded that cocoa fruit peel extract tablets had a faster dissolution time than alkaline peroxide effervescent tablets.